The biogeochemical imprint of the Azores Archipelago lacustrine sedimentary infill. A linkage between the climatic effects of the north Atlantic atmospheric circulation and the tectono-volcanic landscape of the triple junction during the late Holocene - Benavente Marín, Mario (Universitat de Barcelona, 2025)
Programa de Doctorat en Ciències de la Terra / Tesi realitzada a l'Institut de Geociències Barcelona (Geo3BCN-CSIC) [eng] The Azores Archipelago, strategically located in the central North Atlantic, serves as a key location for analyzing regional atmospheric dynamics. Thus, climate reconstructions derived from from sediments of the Azorean lakes are useful for improving our understanding of North Atlantic atmospheric patterns beyond instrumental records. However, the use of such sediments for climate and environmental reconstructions includes complexities, as they are also located in one of the most complex geodynamic regions on the planet. Additionally, early colonization of the archipelago has increased anthropogenic pressure on its ecosystems since settlement. The multi-proxy approach of sedimentary sequences, combined with innovative limnogeomorphic spatial analysis techniques, have facilitated the study of landscape evolution within lake basins of the archipelago and their relationship with the geological substrate. Variable morpho-stratigraphic patterns reflect the morphosedimentary evolution of the depositional environments over the last millennia, within the deep Lake Funda, located on Flores Island, the shallow Lake Caldeirão, on Corvo Island, and the small Lake Caveiro, on Pico Island. The biogeochemical imprint of the sediments from these lakes was variable due to different morphologies of the lake-catchment systems. Furthermore, accelerated sedimentary responses of the systems revealed the increasing anthropogenic transformation of the landscape. The tectono-volcanic configuration of the lake basins modulates the sedimentary responses to hydroclimate and deforestation in the archipelago, emphasizing some effects over others. Verticalized topo-bathymetric morphologies in Funda and the first stages of Caveiro lake-catchment systems evolved with enhanced sediment cascading and reduced evapotranspiration after deforestation that provoked lake deepening. In contrast, the horizontal reliefs of the flat ...